The differences in physical fitness levels between hearing and visually impaired students - Abdullah, Nagoor Meera; Mohamed, Mawarni; Tumijan, Wahidah; Parnabas, Vincent; Ponnusamy, Vellapandian; Mohamed Shapie, Mohamed Nizam; Omar Fauzee, Mohd Sofian (Springer, 2015)
The purpose of the study is to identify the differences of fitness profile between students with hearing impairment and students with visual impairment at secondary schools. A number of 62 subjects from two types of disabilities with 30 students who have hearing impairment (male = 21; female = 9) and 32 students with visual impairment (male = 18; female = 14) voluntarily participated in the study. A fitness profile was determined to identify the fitness level between two types of disabilities. Seven fitness tests were conducted on both groups such as 1600-m run test, 10-m agility run test, standing broad jump test, vertical jump test, handgrip strength test, sit and reach test, and sit-up test. The findings showed that students who are visually impaired performed better in sit-up test (36.50 ± 11.02), 1600-m run test (11.53 ± 2.26), and sit and reach test (31.09 ± 5.04) and students with hearing impairment performed better in handgrip strength test (right hand 29.27 ± 10.57) (left hand 27.48 ± 9.55), standing broad jump test (176.03 ± 43.26), and vertical jump test (40.00 ± 12.81) but with both groups showed similar strength in agility test. There was a significant difference in the sit-up test between two groups (0.0000, p ˃ 0.05), whereas other tests did not show much difference.